Oil Price Shocks and Stock Market Responses: Evidence from Saudi Arabia and Spain - Alzamel, Hussah Adnan; Othman, Jaizah (International Journal of Energy Economics and Policy, 2025)
This research examines the time effect of oil price volatilities on the stock market performance in Saudi Arabia and Spain, which is a net oil exporter and importer, respectively. The overall data of January 2014 to June 2024 were analyzed with the autoregressive distributed lag (ARDL) model to establish short and long-term effects. The results indicate a stable positive relationship between oil prices and stock returns in Saudi Arabia, due to the high reliance of the economy to oil revenues. Spain showed a less consistent and more fluctuating connection that was a testimony to its diversified industrial structure and refined export capacity of oil. Saudi Arabia’s stock market took a negative turn amidst the COVID-19 pandemic in response to the increase in oil prices, as increased uncertainty and investor distrust were witnessed, while such an increase on Spain’s market took a positive shift, as the increase in oil prices is an indicator of recovery of global demand. Volatility was generally low in pre-pandemic conditions but intensified during the crisis, especially in Spain. The results highlight the asymmetric and time-varying effects of oil price shocks on exporters and importers. These findings provide useful insights for investors and policymakers seeking to manage oil-induced risks and design strategies for financial stability under both normal and crisis conditions.